Microbiological characterisation and impact of suspended solids on pathogen removal from wastewaters in dairy processing factories. Issue 3 (29th August 2018) - Fitzhenry, Kelly; Rowan, Neil; Finnegan, William; Zhan, Xinmin; Clifford, Eoghan
Abstract : In this Research Communication we investigate the microbiological profile of 12 dairy wastewater streams from three contrasting Irish dairy processing factories to determine whether faecal indicators/pathogens were present and in turn, whether disinfection may be required for potential water reuse within the factory. Subsequently, the impact of suspended solids on the inactivation efficiency of Escherichia coli via two means of ultravoilet (UV) disinfection; flow-through pulsed UV (PUV) and continuous low pressure UV (LPUV) disinfection was analysed. Faecal indicators total coliforms and E. coli were detected in 10 out of the 12 samples collected at the dairy processing factories while pathogenic bacteria Listeria monocytogenes was detected in all samples collected at 2 out of the 3 factories. Salmonella spp . was undetected in all samples. The results also indicated that organic dairy wastewater solids had an impact on the performance efficiency of the PUV system and, to a lesser extent, the LPUV system. The findings indicate that the targeting of key pathogens would be required to enable wastewater reuse (and indeed effluent discharges if regulation continues to become more stringent) and that LPUV may offer a more robust disinfection method as it appears to be less susceptible to the presence of suspended solids.